Aerospace series. Connector, electrical and optical, rectangular, modular, rectangular inserts, operating temperature 175°C (or 125°C) continuous. Plug, size 2, with mounting holes, class A, C and E. Product standard Part 022, (30th November 2015) - British Standards Institution,
No abstract available